EXD2: A new regulator of mitochondrial translation and potential target for cancer therapy. (4th May 2018) - Stracker, Travis H.
ABSTRACT: In recent work we identified Exonuclease 3′−5′ domain-containing protein 2 (EXD2) as an RNase required for efficient mitochondrial translation. Here I describe in brief the cellular phenotypes caused by EXD2 deficiency and make the case that EXD2 inhibitors could be valuable agents for cancer therapy.